2007
DOI: 10.1002/ibd.3780060307
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis: Implications for inflammatory bowel disease

Abstract: Summary: Cells of the intestinal mucosa live in a harsh environment and therefore rely heavily on the highly regulated process of cell death, apoptosis, to maintain tissue integrity. Imbalance in the intracellular events that modulate apoptosis may contribute to the pathogenesis of inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 184 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…However, IBD patients develop a dysfunction in apoptosis [2325], that can contribute an increased incidence of colorectal carcinoma, and chemotherapy cytotoxicity of the gut epithelia. Apoptosis can be initiated from cell cycle activation [2627], cytokine production [28], infective agents [29], or as an adverse response to drugs [3031].…”
Section: Discussionmentioning
confidence: 99%
“…However, IBD patients develop a dysfunction in apoptosis [2325], that can contribute an increased incidence of colorectal carcinoma, and chemotherapy cytotoxicity of the gut epithelia. Apoptosis can be initiated from cell cycle activation [2627], cytokine production [28], infective agents [29], or as an adverse response to drugs [3031].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a programmed cell death, which under homeostatic conditions exists in harmony with cellular mitosis. Experimental NEC is associated with increased enterocyte apoptosis [12]. We therefore hypothesize that colonization of the intestine by ES may contribute to the pathogenesis of NEC by stimulating release of inflammatory factors and induction of enterocyte apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…CD represents a T‐helper (Th)1‐mediated condition because mucosal immune cells from affected individuals secrete interferon‐γ and tumor necrosis factor (TNF) as well as interleukin (IL)‐12 and IL‐18, but not Th2‐type cytokines 11. Moreover NF‐κB appears to have an important role in CD,12 and several studies have shown that lamina propria T lymphocytes (LPL) from CD patients, compared with LPL from noninflammatory intestinal mucosa, were significantly less susceptible to apoptosis in response to different pro‐apoptotic stimuli 13,14. In CD, there is an imbalance of the anti‐apoptotic mitochondrial protein Bcl‐2 and the pro‐apoptotic mitochondrial protein Bax14,15 as well as a reduction of caspase 3 activity 16.…”
mentioning
confidence: 99%